ENTREPRENEURIAL ORIENTATION (EO) IN INTERNATIONAL BUSINESS: A CASE STUDY OF FISHERIES INDUSTRY IN BALI - Renaldi Ega Hendrawan; Aluisius Hery Pratono; Suyanto Suyanto (CALYPTRA, 2018)
This research aims to explore international entrepreneurial orientation (IEO) in fisheries export industry in Bali which comprises of innovativeness, proactiveness, and risk-taking aspects with one international verbiage variable of strategic performance. The researcher conducted in-depth interviews with seven companies in Bali to understand how the industry stack-up if seen from three aspects of IEO with one additional international verbiage.The result shows that the observed fisheries industry in Bali is an industry that shows negative innovativeness, positive proactiveness, inconsistent risk-taking, and positive strategic performance. Negative innovativeness is solely due to the nature of the industry where the businesses are only exporting raw fish material and further processing takes place at level of importer; positive proactiveness to outpace its competitors; inconsistent risk-taking due to the sector of live or frozen fish; and positive strategic performance because have been an established business.